Insight into the validity of Leptobrachium guangxiense (Anura: Megophryidae): evidence from mitochondrial DNA sequences and morphological characters - Chen, Weicai; Zhang, Wei; Zhou, Shichu; Li, Ning; Huang, Yong; Mo, Yunming (Zootaxa, 2013)
Leptobrachium guangxiense Fei, Mo, Ye and Jiang, 2009 (Anura: Megophryidae), is presently thought to be endemic to Shangsi, Guangxi Province, China. A molecular phylogenetic analysis and morphological data were performed to gain insight into the phylogenetic position of this species. Maximum parsimony, maximum likelihood, and Bayesian inference methods were employed to reconstruct phylogenetic relationship, using 1914 bp of sequences from mtDNA genes of 12S rRNA, tRNAVal and 16S rRNA. Topologies revealed that L. guangxiense and Tam Dao (Vietnam) L. chapaense lineage (3A) formed a monophyletic group with well-supported values. The uncorrected p-distance of ~1.4k bp 16S rRNA data-sets between Tam Dao L. chapaense lineage (3A) and L. guangxiense is only 0.1%. Morphologically, L. guangxiense and Tam Dao L. chapaense lineage (3A) shared the same characters, and are distinguishable from “true” L. chapaense from the type locality in Sa Pa, Vietnam. Based on morphological characters and mitochondrial DNA, we suggested that the Tam Dao lineages of L. chapaense are conspecific with L. guangxiense. This represents a range extension for L. guangx-iense, and a new country record for Vietnam.